2021
DOI: 10.57040/asshj.v2i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing uptake of career counselling services among university students in Nairobi City County, Kenya

Abstract: Failure to take up career counselling services among university students continues to be a concern for learning institutions and policy makers. The concern has been marked by policy interventions aimed at ensuring graduates access career information. In Kenya, universities have developed policies and programmes that encourage uptake of career counselling services. Despite these attempts, there has been minimal uptake of the services among students. The purpose of the study was to assess the level of uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…These results were in accordance to Amani and Mkumbo (2018), who asserted that children were more likely to pursue fulfilling or profitable occupations if their parents were having financial difficulties or are not happy in their jobs. The findings, however, were in conflict with a study by Mwaa (2016), which found that parental socioeconomic factors had no impact on student's awareness of careers since parents would motivate their children to pursue the careers of their preference by providing appropriate educational resources and opportunities for their career growth.…”
Section: Family Determinants Of Career Awareness Among Studentscontrasting
confidence: 79%
“…These results were in accordance to Amani and Mkumbo (2018), who asserted that children were more likely to pursue fulfilling or profitable occupations if their parents were having financial difficulties or are not happy in their jobs. The findings, however, were in conflict with a study by Mwaa (2016), which found that parental socioeconomic factors had no impact on student's awareness of careers since parents would motivate their children to pursue the careers of their preference by providing appropriate educational resources and opportunities for their career growth.…”
Section: Family Determinants Of Career Awareness Among Studentscontrasting
confidence: 79%
“…§ Technical Training: In a calculated attempt to address biting youth unemployment and wide spread of deviance in the country, governments at various levels established technical training schools. Some renew the existing ones to meet the challenges of skill acquisition for the myriad unemployed youths (Blankenship, 2015;Verchueren, 2020;Newa, Kathungu & Wagarga, 2021). § Challenges of Social Security Scheme: As explained by Kotiikaff, Solman and Moeller (2015), the following are the challenges of social security in Nigeria (Makuya & Salum, 2021).…”
Section: Social Security Programmesmentioning
confidence: 99%
“…Mass media has been acknowledged for carrying out certain essential functions in the society. These include informing and shaping public opinion about issues of concern (Peterson, 2006;Owolabi, 2023;Newa et al, 2021;Chukwuma, 2022). Further, mass media is increasingly being utilised as an avenue for targeting behaviour change among audiences (Emojong' & Korir, 2022).…”
Section: Introductionmentioning
confidence: 99%